Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T14:12:39+01:00
-5x+3y+4=0
-12y-2x=8

-5x+3y=-4|*4
-2x-12y=8

-20x+12y=-16
-2x-12y=8
-22x=-8
x=0,5

-5*0,5+3y=-4
-2,5+3y=-4
3y=-1,5
y=-0,5

2010-02-04T14:14:45+01:00
-5x+3y +4 = 0 /*4
-12y - 2x = 8

-20x + 12y + 16 =0
-12y - 2x = 8

-20x = -16
-2x = 8

-22x = -8 / - 22
x=0, (36)


2010-02-04T14:23:01+01:00
-5x+3y+4=0 i -12y-2x=8

-5x+3y+4=0
-12y-2x=8

-5x+3y=4=0
-2x+12y=8 /*-2.5

-5x+3y=-4
5x+12y=20

-5x+3y=-4
15y=16 /:15

-5x+3y=-4
y=1.1

-5x+3y=-4 /*-4
-2x+12y=8


-5x-12y=16
-2x+12y=8

-5x-12y=16
-7x=24 /:-7

-5x-12y=16
x=3,4


x=3,4
y=1,1



;))